IMPROVEMENT OF METHODS OF MANAGING ASSETS AND LIABILITIES OF COMMERCIAL BANKS - Ismatov Bakhriddin Kutbidinovich (American Journals, 2023)
This article talks about commercial banks, methods of managing their assets and liabilities, and ways to improve them.
Keywords: assets and liabilities, profitability, commercial banks, resource base, economy, eminent